(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to know the possibility of applying the three-line model issued by the Institute of Internal Auditors (IIA) in insurance companies. The main research problem was the possibility of applying the three-line model issued by the IIA to insurance companies. The research relied on the inductive, descriptive, and analytical approach by creating a checklist to analyze companies’ data and reach its results. The results showed that insurance companies were not aware of the three-line model issued by (IIA) as a framework for governance, risk management, and internal control, the possibility of adopting the three-line model issued by (IIA) in insurance companies due to acceptance by respondents to the checklist, and the necessity of holding workshops and courses for cadres working within the lines within the company and supporting bodies to contribute to strengthening the work of governance, risk management, and internal control to help achieve the set goals.